Cordez, Philippe. Treasure, Memory, Nature. Church Objects in the Middle Ages. London-Turnhout: Brepols-Harvey Miller Publishers, 2020 [ISBN: 978-1-912554-61-4] - García García, Francisco de Asís (Eikón / Imago, 2022)
Reseña de la obra de Cordez, Philippe. Treasure, Memory, Nature. Church Objects in the Middle Ages. London-Turnhout: Brepols-Harvey Miller Publishers, 2020 [ISBN: 978-1-912554-61-4]